A distinctive new species of wood lizard (Hoplocercinae, Enyalioides) from the Yanachaga Chemillen National Park in central Peru - Venegas, Pablo J.; Duran, Vilma; Landauro, Caroll Z.; Lujan, Lesly (Zootaxa, 2011)
We describe a new species of Enyalioides from a mid-elevation premontane forest in central Peru. This represents the seventh species of Enyalioides known to occur east of the Andes in South America; the other six species are E. cofanorum, E. laticeps, E. microlepis, E. palpebralis, E. praestabilis, and E. rubrigularis. Among other characters, the new species is distinguished from other Enyalioides by the combination of an orange blotch on the antehumeral region (in adult males), 30 or fewer longitudinal rows of dorsals in a transverse line between dorsolateral crests at midbody, ventral scales strongly keeled, and caudal scales heterogeneous in size on each autotomic segment. The new species is most similar morphologically to E. cofanorum and E. microlepis.